Dynamic Visualization of Dendritic Cell-Antigen Interactions in the Skin Following Transcutaneous Immunization - Rattanapak, Teerawan; Birchall, James C.; Young, Katherine; Kubo, Atsuko; Fujimori, Sayumi; Ishii, Masaru; Hook, Sarah (PLOS ONE, 2014)
Delivery of vaccines into the skin provides many advantages over traditional parenteral vaccination and is a promising approach due to the abundance of antigen presenting cells (APC) residing in the skin including Langerhans cells (LC) and dermal dendritic cells (DDC). However, the main obstacle for transcutaneous immunization (TCI) is the effective delivery of the vaccine through the stratum corneum (SC) barrier to the APC in the deeper skin layers. This study therefore utilized microneedles (MN) and a lipid-based colloidal delivery system (cubosomes) as a synergistic approach for the delivery of vaccines to APC in the skin. The process of vaccine uptake and recruitment by specific types of skin APC was investigated in real-time over 4 hours in B6.Cg-Tg (Itgax-EYFP) 1 Mnz/J mice by two-photon microscopy. Incorporation of the vaccine into a particulate delivery system and the use of MN preferentially increased vaccine antigen uptake by a highly motile subpopulation of skin APC known as CD207+ DC. No uptake of antigen or any response to immunisation by LC could be detected.